2020
DOI: 10.1007/s42452-020-03951-0
|View full text |Cite
|
Sign up to set email alerts
|

Marsectohexol and other pregnane phytochemicals derived from Gongronema latifolium as α-amylase and α-glucosidase inhibitors: in vitro and molecular docking studies

Abstract: This study employed in vitro and in silico techniques to screen isolated pregnane phytochemicals (P1-P4), as well as their source pregnane-rich chromatographic fractions, which were derived from Gongronema latifolium Benth (GLB), for their inhibitory potentials against α-amylase, α-glucosidase, and sucrase enzyme activities. The results show that, most pregnane-rich chromatographic fractions and isolated compounds exhibited good inhibitory activities against α-amylase, and α-glucosidase enzymes. Among the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…was reported. The observed inhibitory activity of the pregnane-rich plant extracts against the porcine pancreatic amylase in vitro ( Figure 2 ) and that of the isolated SPPs ( Figure 3 ) was expected as the fraction F1 (previously combined Fr.5 and Fr.6) is the source chromatographic fraction of compounds P1 and P2, while the F3 (derived from further fractionation of Fr.8) afforded P3 and P4 as reported earlier ( Gyebi et al, 2018 ; Ogunyemi et al, 2020 ). Depending on the experimental conditions, several studies have reported the range of alpha-amylase and alpha-glucosidase inhibitory activity of acarbose as 55%–82% ( Mohamed et al, 2012 ; Perez-Gutierrez and Damian-Guzman, 2012 ; Olubomehin et al, 2013 ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…was reported. The observed inhibitory activity of the pregnane-rich plant extracts against the porcine pancreatic amylase in vitro ( Figure 2 ) and that of the isolated SPPs ( Figure 3 ) was expected as the fraction F1 (previously combined Fr.5 and Fr.6) is the source chromatographic fraction of compounds P1 and P2, while the F3 (derived from further fractionation of Fr.8) afforded P3 and P4 as reported earlier ( Gyebi et al, 2018 ; Ogunyemi et al, 2020 ). Depending on the experimental conditions, several studies have reported the range of alpha-amylase and alpha-glucosidase inhibitory activity of acarbose as 55%–82% ( Mohamed et al, 2012 ; Perez-Gutierrez and Damian-Guzman, 2012 ; Olubomehin et al, 2013 ).…”
Section: Discussionsupporting
confidence: 77%
“…Three bioactive pregnane-rich chromatographic fractions and the isolated steroidal pregnanes were selected for the current study. The isolated pregnane compounds comprise a pregnane marsectohexol (P1) and three pregnane glycosides, viz: iloneoside (P2), 3-O-[6-deoxy-3-O-methyl-β-D-allopyranosyl-(1→4)-β-D-oleandropyranosyl]-17β-marsdenin (P3), and 3-O-[6-deoxy-3-O-methyl-β-D-allopyranosyl-(1→4)-β-D-canaropyranosyl]-17β-marsdenin (P4) ( Gyebi et al, 2018 ; Ogunyemi et al, 2020 ) as depicted in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethnopharmacological uses of herbs, spices, and medicinal plants are due to their wide range of biological activities in human health and diseases [61][62][63]. Among these, Vernonia amygdalina and Occinum gratissimum and their extracts have been extensively reported for their antiviral activities in vitro [19,20,22]; and thereby may be suggested as vegetal resources for bioactive compounds for the development of preventive nutraceuticals and drug candidates in COVID-19 infection [23].…”
Section: Discussionmentioning
confidence: 99%